HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN PROKRASTINASI AKADEMIK SISWA MAS AL WASHLIYAH 12 PERBAUNGAN TAHUN AJARAN 2025/2026 - Khairani, Syahila; Sandra Dewi, Ika; Hidayati Hutasuhut, Dina; Ulfa Syaimi, Khairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between peer social support and academic procrastination in class XI IPA students of MAS Al Washliyah 12 Perbaungan in the 2025/2026 academic year. The method used is quantitative correlation with a sample of 43 students selected by simple random sampling. Data were collected through a Likert-scale-based peer social support and academic procrastination questionnaire that has been tested for validity and reliability (peer social support α = 0.881; academic procrastination α = 0.887). Based on data analysis that has been carried out using the product moment correlation test calculation formula, the results of the study were a correlation coefficient (r) of -0.479 and a significance value (p) of 0.001 (p <0.05). The results of this study indicate a relationship between peer social support and academic procrastination in grade XI IPA students at MAS Al Washliyah 12 Perbaungan in the 2025/2026 academic year. The coefficient of determination of 23% indicates that peer social support contributes to academic procrastination in students, while the remaining 77% is influenced by other factors. This finding indicates that the higher the peer social support, the lower the student's academic procrastination. Therefore, strengthening peer social support is important to integrate into educational programs to help students reduce academic procrastination, increase learning motivation, and support optimal social and academic development.